An adaptive flow path regenerator used in supercritical carbon dioxide Brayton cycle. (25th June 2018) - Ding, Miao; Liu, Jian; Cheng, Wen-Long; Huang, Wen-Xu; Liu, Qi-Nie; Yang, Lei; Liu, Shi-Yi
Highlights: An adaptive flow path regenerator used in SCO2 –Brayton cycle is proposed. The pressure loss of the adaptive flow path regenerator can be reduced up to 69%. The effectiveness of the new regenerator can be increased by nearly 2%. The compactness and heat transfer rate of the new regenerator can be improved. The regenerator is manufactured by metal 3D printing and tested by a SCO2 experimental platform. Abstract: The supercritical CO2 recompression Brayton cycle is proposed to be used as a typical application in 4th generation reactors. In the cycle, the performance of the regenerator has a significant impact on the performance of the entire cycle. As the specific heat capacity and density of SCO2 change significantly with the temperature and pressure. Therefore, in this paper, a new adaptive flow path regenerator is proposed and designed in order to further improve the performance of the regenerator, in which the flow path sizes varied with the CO2 density when the CO2 flowing through the regenerator. Firstly, the heat transfer performance and hydraulic performance of the adaptive flow path regenerators are analyzed in detail by simulation, and it is verified in theory that the design of new adaptive regenerator is feasible. Then, a new adaptive flow path regenerator with S-shaped fins is manufactured by metal 3D printing technology and the performances of the new regenerator are tested by a SCO2 experimental platform. The experimental results are consistent with simulation results and show that the performances of the new regenerator are significantly improved: the pressure loss can be reduced up to 69%, the effectiveness can be increased by nearly 2%, and the compactness and heat transfer rate can be improved at the same time.